Crack-induced electrical resistivity changes in cracked CNT-reinforced composites. - Rodríguez de Tembleque, Luis; García-Sánchez, Felipe; García Macías, Enrique; Buroni, Federico C.; Sáez, Andrés (Elsevier, 2020)
Carbon nanotube (CNT)-reinforced composites exhibit a piezoresistive behavior that permits their use as sensors in novel structural health monitoring (SHM) applications, by measuring the electrical resistivity change of the CNT modiﬁed laminate. However, the presence of cracks in such composite materials may not only compromise their struc- tural integrity, but may as well alter their capability to act as reliable piezoresistive sensors. In this paper, we conduct a numerical study aimed at quantifying how the presence of cracks in reinforced polymer composites does inﬂuence their electrical conductivity and, consequently, their sensor performance. To this end, the electromechanical constitu- tive properties of the composite are determined by a mixed micromechanics approach that allows characterizing both the elastic properties and the strain-induced alterations in the overall electrical conductivity of the CNT-reinforced composite. The strain response of the cracked composite domain is accurately determined by means of a dual Boun- dary Element (BE) approach. Electrical conductivity in the cracked composite follows from its computed strain state at each point in the domain. Subsequently, the resulting non-homogeneous electrical conductivity problem is sol- ved using a ﬁnite diﬀerences scheme that also accounts for semipermeable crack-face electrical boundary conditions. Several parametric studies are conducted to illustrate the inﬂuence of various crack geometries in the piezoresistive behavior of CNT-reinforced composites at varying CNTs concentrations.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/12462
Keywords: Piezoelectricidad; Materiales nanocompuestos; Mecánica de fractura; Carbon nanotube; Crack detection; Nanocomposites; Piezoresistivity; Damage identiﬁcation